A New Historical Approach to Learn the Madheshi People in Nepal - Karna, Manoj Kumar (Historical Journal, 2023)
Nepal is a multicultural country with a different physical geography. The people living in Himalayan; mountain and valley, and in the flat plain/Terai (Madhesh) regions have their mother tongue and even the different dialects in the same Nepali language. Despite the contribution of the Madheshi people in the nation-building and their continuous effort to maintain harmony with the other communities, some ruling people from non-Madheshi communities continuously have been denying their presence by ignoring cultural assimilation in the sectors like history, university texts, media, bureaucracy, security, the power structure in the nation, and so on which creates sometimes unrest and the hostility. The anti-Madheshi narrative used by many historians has left the Madheshi people always a suspicious community in Nepal in terms of nationality for those citizens who are unaware of the truth of Nepali history. So, this academic writing uses new theoretical tools like new historicism with some other marginal theories for the historical truths and to counterfeit the pre-histories to maintain cultural assimilation. It is a qualitative research rendering through historical text, article, theoretical text, and news media to crosscheck the facts of either community of Nepal.